2023
DOI: 10.3390/molecules28020834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on the Self-Assembly of Wheat Gluten Polypeptide

Abstract: Self-assembled fibrillation of wheat gluten is a common phenomenon in the daily production and processing of wheat flour products. The driving forces for its formation and the factors that influence the morphology of fibrils have not been thoroughly investigated. In this study, the effect of three bonding changes (breaking hydrogen bonds, strengthening hydrophobic interactions, and SH-SS exchange reactions) on gluten polypeptide (GP) fibrillation was simulated by adjusting the heating temperature (room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The results indicated a gradual increase in the proportion of aggregates and β-sheet structures, accompanied by a decrease in the proportion of α-helix and random oil structures in the thermally induced formation of AFs gluten . Aggregation signifies a high density of β-sheet, serving as the predominant structure in AFs . Consistent with these findings, Bruun et al observed that cooking wheat gluten or treating it with transglutaminase led to a transition in protein structure from α-helix to β-sheet.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The results indicated a gradual increase in the proportion of aggregates and β-sheet structures, accompanied by a decrease in the proportion of α-helix and random oil structures in the thermally induced formation of AFs gluten . Aggregation signifies a high density of β-sheet, serving as the predominant structure in AFs . Consistent with these findings, Bruun et al observed that cooking wheat gluten or treating it with transglutaminase led to a transition in protein structure from α-helix to β-sheet.…”
Section: Resultsmentioning
confidence: 74%
“…Aggregation signifies a high density of β-sheet, serving as the predominant structure in AFs. 49 Consistent with these findings, Bruun et al 50 observed that cooking wheat gluten or treating it with transglutaminase led to a transition in protein structure from α-helix to β-sheet. The three β-strand-rich structures in AFs glutenin before and after cooking exhibited increases of 2.50, 4.11, and 3.42% in aggregation, β-sheet, and antiparallel β-sheet, respectively.…”
Section: Average Size and ζ Potential Measurementsmentioning
confidence: 77%
“…However, CLSM analysis of the gluten network structure at the periphery of the pores revealed that the UT treatment led to a more prominent aggregation of the gluten network and significantly higher ( P < 0.05 ) gluten network junction point than the CMT treatment (Table S1). Increasing drying temperature led to the denaturation and aggregation of higher levels of gluten into larger polymeric proteins, resulting in a more compact and continuous gluten network structure stabilised by hydrogen and disulphide bonds (Liu et al ., 2023). In contrast, the larger pores in the cross section of the UT samples than the CMT samples might be attributed to the UT‐mediated increase in the aggregation of the gluten network.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it contributes to narrowing the optical band gap of FCNMs, followed by the emission in the far red or near IR region with high uorescence quantum yield. [69][70][71][72][73][74] Other atoms like selenium, boron, and uorine are also utilized for shiing the wavelength to the red region aer doping at edges on the surface of the organic precursor. The band gap is opened by the incorporation of these heavy atoms into the carbon core.…”
Section: Crucial Aspects For the Synthesis Of Red-emitting Fcnmsmentioning
confidence: 99%